2019
DOI: 10.3390/nu11092127
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Fat-Accelerating Leptin Signaling Promotes Protumorigenic Gastric Environment in Mice

Abstract: Excess of fat intake leads to obesity and causes a variety of metabolic diseases and cancer. We previously demonstrated that high-lard diet induces intestinal metaplasia, a precancerous lesion of the stomach mediated by leptin signaling. This study aims to investigate which kinds of dietary fat cause the intestinal metaplasia onset. We fed eight kinds of high-fat diets (HFDs) of animal or plant origin to mice evaluated their effect on gastric pathogenesis. Five types of dietary fat were divided according to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 51 publications
(64 reference statements)
0
9
0
Order By: Relevance
“…26 Dietary fat-accelerating LEP signaling was shown to promote protumorigenic gastric environment in mice. 27 Overexpression of LEP was linked with the development of GC in humans and murine. 25,28 Serum LEP levels were related with insulin resistance in GC patients 29 and may be a valuable diagnostic indicator.…”
Section: Introductionmentioning
confidence: 99%
“…26 Dietary fat-accelerating LEP signaling was shown to promote protumorigenic gastric environment in mice. 27 Overexpression of LEP was linked with the development of GC in humans and murine. 25,28 Serum LEP levels were related with insulin resistance in GC patients 29 and may be a valuable diagnostic indicator.…”
Section: Introductionmentioning
confidence: 99%
“…The ferroptosis process is iron-dependent and is characterized by increased lipid active oxygen ( 71 ). A recent study showed that a high-lard diet induced IM ( 72 ). Therefore, the accumulation of lipid active oxygen induced by ferroptosis may be an important IM mechanism at the gastric epithelium, hence, preventing ferroptosis in epithelial cells may be effective in preventing gastric epithelial IM.…”
Section: Discussionmentioning
confidence: 99%
“…74 This further supports a role for H pylori in accelerating gastric cancer development with the yes-associated protein 1, a key effector of the Hippo pathway, also being implicated in the process (Figure 3B). 75 HFD also has been shown induce gastric dysbiotic changes including increased Lactobacillus abundance, intestinal metaplasia, expression of leptin, phosphorylated leptin receptor Q21 and STAT3 and intracellular b-catenin accumulation (Figure 3B), 76,77 whereas loss of the leptin receptor attenuates the effect of HFD on dysbiosis and intestinal metaplasia. 77…”
Section: Microbial Involvement In Gastric Carcinogenesis: Mechanistic Insightsmentioning
confidence: 92%
“…[73][74][75] In GC, a HFD induces gastric dysbiosis (characterized by increased Lactobacillus abundance), intestinal metaplasia, the expression of leptin, phosphorylated leptin receptor and STAT3 and intracellular b-catenin accumulation. 76,77 (C) In the context of CRC, certain microbes such as pks Q41 þ E coli, P anaerobius, and B fragilis are able to produce toxins that can influence carcinogenic processes. These include the induction of the DNA damage checkpoint pathway and proinflammatory responses, TLR interaction, impairment of the antitumor T-cell response, nuclear factor-kB (NF-kB), and Wnt/b-catenin pathway activation, further promoting cell proliferation.…”
Section: Q40mentioning
confidence: 99%